Dental pain and associated factors in 2 to 4-year-old children in Goiânia - Marília Galvão Chaves Lemes; Maria do Rosário Gondim Peixoto; Ida Helena Carvalho Francescantonio Meneses; Maria do Carmo Matias Freire (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: To investigate the prevalence of dental pain and associated factors in 2-4-year-old children in Goiânia (GO). METHODS: Cross-sectional study using home interviews with parents or guardians and anthropometric measures. The sample consisted of 385 children from 2 to 4 years old. The variables analyzed were: dental pain sometime in their lives, and demographic, socioeconomic and health-related factors (health condition, diet, nutritional status and behavior). Bivariate analysis and logistic regression were performed, based on a hierarchical model for risk assessment, considering the sample weights. RESULTS: Dental pain prevalence was 9.9% (95%CI 7.4 - 13.1). After adjustment for other variables, children whose mothers had low education level and those who regularly consumed artificial powder juice containing sugar were more likely to have dental pain (OR = 3.03 and 2.15, respectively). CONCLUSION: It was concluded that one in ten children had dental pain, and the prevalence was associated with low education level of the mother and the regular consumption of artificial powder juice.